KESULITAN BELAJAR PESERTA DIDIK DALAM MEYELESAIKAN SOAL CERITA SPLTV BERBASIS PEMECAHAN MASALAH - Nurul Ikhsan Karimah; Elva Mariza; Laelasari Laelasari; Dian Permana Putri (Jurnal Karya Pendidikan Matematika, 2022)
Many students' perceptions indicate that mathematics is a difficult subject because it is always related to formulas and calculations. In addition, many students still have difficulty in solving story problems so that many make mistakes in doing them. Therefore, this study aims to describe the learning difficulties experienced by students in solving story problems, one of which is SPLTV material. This study uses a qualitative approach with a descriptive method. Procedures for data collection through tests, interviews, and documentation. The results showed that the biggest difficulty experienced by students was difficulty in performing mathematical procedures with a percentage of 74%. The contributing factors are because students are less careful in carrying out calculations, using incorrect arithmetic operations resulting in inaccurate answers and the completion process is less clear, and inaccuracy in concluding the final answer